STRUKTUR PENDAPATAN DAN TINGKAT KESEJAHTERAAN PETANI PADI ORGANIK DI KABUPATEN LAMPUNG TENGAH - Julica Samara; Dwi Haryono; Ktut Murniati (Politeknik Negeri Lampung, 2022)
This research aimed to analyze the income of organic rice farmers, household income of organic rice farmers, and the level of prosperity of organic rice farmers in Central Lampung Regency. The research method used in this study was the survey method. This research was conducted in Central Lampung Regency. The research location was chosen purposively with the consideration that in Central Lampung Regency there were still farmers who planted organic rice in three districts, namely Trimurjo District, Punggur District, and Seputih Raman District. Respondents were all farmers who planted organic rice in three districts with 31 farmers taken by census techniques. The data collection was carried out in January - March 2020. Data analysis used in this research was a qualitative and quantitative descriptive method. The result showed that the level of income of organic rice farmers in Central Lampung Regency was Rp41.166.291,54 per year. The level of household income of organic rice farmers in Central Lampung Regency was Rp89.906.452,83 per year. Based on the criteria of the Central Statistics Agency (BPS) in 2014, prosperity level of all organic rice farmers in Central Lampung Regency fell into prosperous category.